RISET PLAGIARISME MAHASISWA AKUNTANSI : SYTEMATIC LITERATURE REVIEW - Mulia Rahmah; Nurmala Ahmar (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
Plagiarism is an act of academic fraud that often occurs among students. The purpose of this research is to map research topics, research methods, and research subjects from journals found by researchers. The results of this study indicate that there are four published topics that have been determined by researchers based on the journals collected. The most widely used methods are surveys and questionnaires, while the subjects are students.